Potensi Cendawan Endofit Padi Lokal Sulawesi Selatan Sebagai Penghasil Siderefor - S Syamsia; Abubakar Idhan; Amanda Patappari Firmansyah; N Noerfitryani (JURNAL GALUNG TROPIKA, 2020)
Siderophore is an iron-chelating agent produced by plants and microorganisms under iron deficiency conditions. One of the microorganisms that ability produce siderophore is a fungus. This study aimed to determine the potential of endophytic fungi in creating siderophore. The ability of fungi to produce siderophore, especially Salicylate and Catechol using Potato Dextrose Broth (PDB) liquid media and Hathway Reagent. Eight isolates of endophytic fungi from local rice South Sulawesi have tested their ability to produce siderophore. Eight isolates of endophytic fungi before being tested were rejuvenated by growing on Potato Dextrose Agar (PDA) medium for seven days. Each isolate was grown on a PDB medium before being tested. The absorbance is measured using a spectrophotometer at a wavelength of 560 nm with Na. Salicylate 700 nm with 2.3 DHBA as standard. The results showed that the isolates of E4 and E8 had the capability to produce siderophores. The results provide the latest information regarding endophytic fungi' potential from local rice in South Sulawesi as a siderophore producer.